Avaliação temporal dos padrões ecológicos de distribuição das assembleias de peixes do alto rio Paraná, Brasil. - Gutiérrez Cortés, Ángela Liliana (2015)
Studies aiming to understand the patterns of species distribution have been developed to different ecosystems of the planet. There is a sharp increase in studies that consider spatial and temporal scales, in order to include all sources of variation. Tropical aquatic ecosystems not only are recognized by high diversity and ecological complexity, but also because the high degree of derived degradation of human activities. Evaluating the variations of the attributes of these communities, such as variations in structure and beta diversity in different groups of organisms allow create a theoretical framework that serves as the basis for conservation policies. In here, I analyzed the general patterns of fish communities in the floodplain of the upper Parana River. I explored data of floodplain fish communities collected over 13 years of sampling focusing in: i) the contribution of environmental conditions as well as the spatial and temporal scales, the structure of fish communities, and ii) the relationship of beta diversity of fish communities with environmental heterogeneity, mediated by the occurrence of annual periods of flood and drought. Total assembly was analyzed (total taxonomic matrix) and the trophic and reproductive guilds separately to detect differences in responses according to the approach. I confirmed that changes in environmental heterogeneity derived from the annual periods with different hydrological cycles, exerted influence in the structure of fish communities, regardless their functional characteristics. The magnitude of this effect varies among the guilds, being higher in the species with low dispersal ability (herbivores, insetivores, invertivores and onivores). In addition, I demonstrated that the temporal scale also had an effect in all communities, especially in the species belonging to guilds with high dispersal ability (migratory, piscivores, detritivores). A positive relationship was found between beta diversity and environmental variation for some trophic guilds (detritivores, piscivores, herbivores), as well as between beta diversity and the effect generated by the occurrence of dry periods in lowland environments (migratory species, invertivores). However, only one guild (insectivores) presented a negative relationship between beta diversity and environmental heterogeneity. In conclusion, generalizations can not be made because the relationship depends on the functional traits (trophic and reproductive) that characterize each community analyzed and this may be valid for other groups of organisms. In summary, these results allow us to characterize the response of the different fractions of the assemblies (eg, trophic and reproductive guilds) to the flood pulse occurrence which allows predicting the response to changes that hydrological dynamics in this and other similar systems. This knowledge could provide a solid basis in relation to conservation planning and management of basin fish fauna with flow control.